Managerial decision styles of deans: a case study of a Malaysian Public University / Leele Susana Jamian, Gurnam Kaur Sidhu and Parmjit Singh Aperapar. - Jamian, Leele Susana; Sidhu, Gurnam Kaur; Aperapar, Parmjit Singh (Universiti Teknologi MARA Cawangan Selangor, 2011)
It is often said that decision making style (DMS) is reflective of leadership style. Numerous studies in the area of Management and Leadership indicate that DMS is a key factor that contributes to the success of both managers and their organizational performance. Using the Decision Making Styles Inventory (DMSI) developed by Rowe and Boulgarides (1992), this paper examines the managerial DMS ofdeans in one of the Malaysian public universities. The scores derived from the DMS were categorized into four decision styles, namely directive, behavioural, analytical and conceptual. The findings revealed that a majority of the deans adopted at least one very dominant or dominant DMS, i mainly behavioural DMS, along with one or two back-up decision styles. Nevertheless, the overall individual results further revealed that the deans possessed more than one style implying that they have considerable flexibility in their managerial DMS and are able to change their decision styles from one situation to another with little difficulty.